2015
DOI: 10.15376/biores.10.3.3963-3978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Boron Impregnation and Heat Treatment on Some Mechanical Properties of Oak (Quercus petraea Liebl.) Wood

Abstract: Heat treatment changes some physical, mechanical, and chemical properties of wood. Inorganic borates have been used as wood preservatives for many years. The aim of this study was to investigate the effects of impregnation chemicals on some mechanical properties (bending strength (MOR), modulus of elasticity (MOE), tensile strength parallel to the grain (TS), compression strength parallel to the grain (CS), and shear strength parallel to the grain (SS)) of heat-treated oak (Quercus petraea Liebl.). For this pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
1
26
1
3
Order By: Relevance
“…The main disadvantage of such heat treatments is the reduced strength properties of the end product based on mass loss and chemical degradation of wood (Bekhta and Niemz 2003;Yıldız et al 2006;Korkut et al 2008;Welzbacher et al 2008;Gündüz et al 2010;Pelit et al 2015b;Perçin et al 2015). Furthermore, during heat treatment, wood defects such as cracking (internal and/or surface cracks), collapsing and deformation (e.g., bow, spring, twist, and cup) may occur because of the changes in the anatomical structure of wood (Boonstra et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The main disadvantage of such heat treatments is the reduced strength properties of the end product based on mass loss and chemical degradation of wood (Bekhta and Niemz 2003;Yıldız et al 2006;Korkut et al 2008;Welzbacher et al 2008;Gündüz et al 2010;Pelit et al 2015b;Perçin et al 2015). Furthermore, during heat treatment, wood defects such as cracking (internal and/or surface cracks), collapsing and deformation (e.g., bow, spring, twist, and cup) may occur because of the changes in the anatomical structure of wood (Boonstra et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Such treatments include a two-stage impregnation and heat treatment (Perçin et al 2015;Lahtela and Kärki 2016); magnetization followed by furfurylation (Dong et al 2016); boron impregnation and heat treatment (Kartal et al 2008); densification followed by oil heat treatment (Fang et al 2011(Fang et al , 2012, as well as freezing and heating treatment (Awoyemi et al 2010;Missio et al 2015Missio et al , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Average values for compression strength in L, R, T directions calculated in this study are shown in Table 3. The average compression strength of oak species varies from 51 to 75 N/mm 2 (Berkel 1970, Dündar 2002, Keskin 2004, Munoz and Gete 2011, Perçin et al 2015. Sessile oak used in these tests appears to be somewhat lower in compression strength L direction than average reported in the literature.…”
Section: Resultsmentioning
confidence: 94%